Biofuel production and its quality standards - Nagy, Orsolya (Acta Agraria Debreceniensis, 2013)
The increasing consumption due to the decreasing amount of fossile energy resources, as well as the increasing fuel prices and living standard will justify the better utilisation of the opportunities lying in biofuel production. Certain countries produce biofuels for their own use or they even export them. However, there are countries which have not decided which feedstock and technology to use. Biofuel – mainly biodiesel and bioethanol – use greatly contributes to environmental protection, decreased CO2 emission and reduced greenhouse effect.